RELATIONSHIP OF FAMILY SUPPORT AND MENSTRUAL KNOWLEDGE TOWARD MENARCHE READINESS - Istikomah, Laili; Atika (UNIVERSITAS AIRLANGGA, 2025)
Background: Menarche is the first sign of maturity of the female reproductive organs that requires both physical and psychological readiness. However, in reality, many adolescent girls are not yet physically and mentally prepared when experiencing their first menarche. This lack of readiness often causes problems such as fear, embarrassment, anxiety, and inappropriate behavior in maintaining personal hygiene. It occurs due to limited knowledge about menstruation and the lack of support and open communication from the family, especially the mother. This study aims to analyze the relationship between family support and menstrual knowledge with menarche readiness among elementary school students. Methods: This quantitative study employed a cross-sectional design involving 40 female students selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Fisher’s Exact Test (p < 0.05). Results: The results showed that most female students had suboptimal family support (60%), low knowledge of menstruation (52.5%), and were not ready to face menarche (75%). There was a significant relationship between family support (p-value= 0.001) and knowledge of menstruation (p-value = 0.001) and readiness to face menarche. Conclusion: Family support and good knowledge can improve adolescents' physical and mental readiness for menarche. Collaboration between families, schools, and health workers is needed to provide reproductive health education from pre-puberty age.